Shovel maintenance gains from improved designs, tools, and techniques - Carter, Russell A (Concrete Products, 2001)
A significant portion of shovel downtime is devoted to wire rope repair and replacement. Shovel ropes are subject to constant stress and eventually wear out due to fatigue from repeated bending, vibration, and shockloading, as well as from metal loss caused by the steady sliding and rubbing that takes place during normal usage, or from cable deformation caused by hard contact with rocks, sheaves, or rollers.